1997
DOI: 10.1063/1.872545
|View full text |Cite
|
Sign up to set email alerts
|

Explosion of soliton in a multicomponent plasma

Abstract: A three-dimensional nonlinear Kadomtsev–Petviashvili (K–P) wave equation is derived to discuss the solitons in multicomponent plasma contaminated with negative ions. A new formalism of the simple wave solution method is developed for finding the soliton behaviors caused by the presence of negative ions in plasmas. It is seen that the nonlinear wave equation leads, in some cases, to an ordinary differential equation and a straight way for solving the soliton propagation in plasmas. The overall observations desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 15 publications
0
46
0
1
Order By: Relevance
“…However, this technique, by now, is well established in fluid dynamics in finding the wave solution in inhomogeneous fluid and later many investigators (Ianenko [20]; Pogodin et al [21]; Das [22]) employed this technique to study the acoustic gravity waves in atmosphere. ,The same procedure, with slight modification, has been adopted t o solve the nonlinear wave equation (Das et al [19]) derived in a multicomponent plasma and have shown the novelty of the method to find the nonlinear structure that appears in plasma acoustic waves, Our motivation is to propose the same approach to find the complete soliton solution of the NIK-dV equation. To apply this procedure we use the following transformation…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, this technique, by now, is well established in fluid dynamics in finding the wave solution in inhomogeneous fluid and later many investigators (Ianenko [20]; Pogodin et al [21]; Das [22]) employed this technique to study the acoustic gravity waves in atmosphere. ,The same procedure, with slight modification, has been adopted t o solve the nonlinear wave equation (Das et al [19]) derived in a multicomponent plasma and have shown the novelty of the method to find the nonlinear structure that appears in plasma acoustic waves, Our motivation is to propose the same approach to find the complete soliton solution of the NIK-dV equation. To apply this procedure we use the following transformation…”
Section: Introductionmentioning
confidence: 98%
“…On the other hand, Jones et al [lo] considered a plasma with multi-temperature electrons and has shown that, even for a small percentage of additional multi-temperature electrons, there exist new features in the plasma acoustic modes. However, the salient features of solitons were further studied theoretically by many authors through the derivation of K-dV or K-P [19]). …”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…͑1͒ Of the misleading statements in their paper, the worst is the claim by the authors that the tanh-method, as a novel and simple way of obtaining solitary wave solutions of nonlinear evolution equations in plasma physics, was developed by Das et al 2 Of course, and as is indeed mentioned, the tanh-method and variations thereof have been known in fluid dynamics for a long time, where they amount to a useful rephrasing of properties of the underlying Legendre polynomial structures. In the present context, the tanh-method refers to a technique to find closed-form solutions of nonlinear partial differential equations ͑PDE͒ as polynomials in the ͑independent͒ variable Y ϭtanh , rather than in the wave argument ϭkxϪ tϩ␦ itself.…”
Section: ͓S1070-664x͑99͒02211-9͔mentioning
confidence: 99%